The design and analysis of the dynamics of a mechanical impact fuze for a 40 mm high explosive grenade - Els, Daniel Nicolaas Johannes (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEng.) -- University of Stellenbosch, 1995.